Efektivitas Aplikasi Mobile JKN (Jaminan Kesehatan Nasional) Pada Kantor Badan Penyelenggara Jaminan Sosial Kesehatan Cabang Bengkulu - Nur’aini Firdaus; Harius Eko Saputra; Yusuarsono Yusuarsono (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effectiveness of the Mobile JKN (National Health Insurance) application at the Bengkulu Branch Office of BPJS Health. This research applies a descriptive qualitative method involving two key informants and three main informants. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the effectiveness of the Mobile JKN application is reflected in four indicators: target accuracy, socialization, application objectives, and monitoring. The application facilitates faster and more efficient access to health services for JKN participants, although challenges remain, such as limited public understanding and technical issues within the application. Overall, the Mobile JKN application is considered fairly effective but requires stronger socialization efforts and technical improvements to maximize its benefits for the public.